A simple chemical free arsenic removal method for community water supply - A case study from West Bengal, India - Sen Gupta, B.; Chatterjee, S.; Rott, U.; Kauffman, H.; Bandopadhyay, A.; DeGroot, W.; Nag, N.K.; Carbonell-Barrachina, A.A.; Mukhopadhyay, S. (Elsevier, 2009)
This report describes a simple chemical free method that was successfully used by a team of European and Indian scientists (www.qub.ac.uk/tipot) to remove arsenic (As) from groundwater in a village in West Bengal, India. Six such plants are now in operation and are being used to supply water to the local population (www.insituarsenic.org). The study was conducted in Kasimpore, a village in North 24 Parganas District, approximately 25 km from Kolkata. In all cases, total As in treated water was less than the WHO guideline value of 10 mg/L. The plant produces no sludge and the operation cost is 1.0 US$ per day for producing 2000 L of potable water.